Enriching Sports Traditions At Sman Pakusari Jember: Reviving The Spirit Of Playing Bullet Rejection With A Touch Of Kasti Ball - sabianto, arik; Idrisi , Vahriel Umam M.; Ramadhan , Raya Rayhan; Putra, Ramadhan Rizky Wahyu; Yono , Topo (Journal Of Humanities Community Empowerment, 2024)
This study aims to improve bullet rejection learning at SMAN PAKUSARI JEMBER. Conducted for 4 weeks involving 36 grade 10 students. The observations show limited facilities and infrastructure, so that bullet rejection learning is not optimal. Innovation in learning is carried out with examples of movements from teachers and the use of baseballs as alternative equipment